Defending the Digital Skies: A Survey of Cloud Security Measures (International Journal of Food and Nutritional Sciences, 2022)
In an era marked by the ubiquity of cloud computing, "Defending the Digital Skies: A Survey of Cloud Security Measures" stands as a comprehensive guide to the intricate world of safeguarding data, applications, and infrastructure in the cloud. The relentless expansion of digital landscapes and the evolving threat landscape necessitate a holistic understanding of the security measures designed to fortify cloud environments. This survey paper embarks on a journey through the intricacies of cloud security, offering a panoramic view of the strategies, best practices, and technologies that underpin the protection of digital assets amidst the dynamic cloud ecosystem. The paper commences by unveiling the foundational principles of cloud security, shedding light on the shifting paradigms of threat landscapes and the necessity for adaptive security strategies. It explores the encryption and access control mechanisms that shield data from unauthorized access and underscores the paramount importance of identity and access management in cloud environments.